Democracy and Islam in Indonesia - Mirjam KÃ¼nkler, Alfred Stepan (Columbia University Press, 2013)
The resurgence of religion calls for careful analysis and constructive criticism of new forms of intolerance as well as new approaches to tolerance, respect, mutual understanding, and accommodation. In order to promote serious scholarship and informed debate, the Institute for Religion, Culture, and Public Life and Columbia University Press are sponsoring a book series devoted to the investigation of the role of religion in society and culture today. This series includes works by scholars in religious studies, political science, history, cultural anthropology, economics, social psychology, and other allied fields whose work sustains multidisciplinary and comparative as well as transnational analyses of historical and contemporary issues. The series focuses on issues related to questions of difference, identity, and practice within local, national, and international contexts. Special attention is paid to the ways in which religious traditions encourage conflict, violence, and intolerance and also support human rights, ecumenical values, and mutual understanding. By mediating alternative methodologies and different religious, social, and cultural traditions, books published in this series will open channels of communication that facilitate critical analysis.